2011
DOI: 10.1186/1472-6882-11-36
|View full text |Cite
|
Sign up to set email alerts
|

Patients visiting the complementary medicine clinic for pain: a cross sectional study

Abstract: BackgroundPain is one of the most common reasons for seeking medical care. The purpose of this study was to characterize patients visiting the complementary medicine clinic for a pain complaint.MethodsThis is a cross-sectional study. The study took place at Clalit Health Services (CHS) complementary clinic in Beer-Sheva, Israel. Patients visiting the complementary clinic, aged 18 years old and older, Hebrew speakers, with a main complaint of pain were included. Patients were recruited consecutively on random d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 29 publications
2
13
0
Order By: Relevance
“…Large sample-sized studies ranged from 517 to 31,044 participants (mean: 2,696; median: 1,950), and the small sample-sized studies ranged from 92 to 249 participants (mean: 175; median: 194). Only four studies had small sample sizes and were conducted in clinical settings [60,61,66,67]. Of the large sample-sized studies, 8 were conducted in clinical settings [30,43,[62][63][64][65]68,69] and the remaining 18 were population-based studies [26,29,42,44,45,[47][48][49][50][51][52][53][54][55][56][57][58][59].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Large sample-sized studies ranged from 517 to 31,044 participants (mean: 2,696; median: 1,950), and the small sample-sized studies ranged from 92 to 249 participants (mean: 175; median: 194). Only four studies had small sample sizes and were conducted in clinical settings [60,61,66,67]. Of the large sample-sized studies, 8 were conducted in clinical settings [30,43,[62][63][64][65]68,69] and the remaining 18 were population-based studies [26,29,42,44,45,[47][48][49][50][51][52][53][54][55][56][57][58][59].…”
Section: Resultsmentioning
confidence: 99%
“…Although some other studies with large samples reported on the prevalence of CAM use, they either combined back and neck pain together as a single questionnaire item or considered back pain within the broad category of musculoskeletal pain and as such did not allow extraction of prevalence rates specifically for back pain [48,54,55,57,65]. Of the four studies drawing on small samples, three studies identified prevalence rates of CAM use for back pain within a range of 5.6% to 62.7% (mean: 38.3%; median: 46.6%) [60,61,66]. One of the small sample-sized studies, while investigating the use of CAM for chronic pain, reported the prevalence of back pain in the Cross-sectional (n51,310), population sample but did not specify the prevalence rate of CAM use specifically for back pain [67].…”
Section: Prevalence Of Cam Usementioning
confidence: 98%
“…[17][18][19][20] Comparing results from these studies with those from the present study requires caution about the generalizability to subsets of the population of members with different types of pain seeking CAM services in an IHDS. In addition, because we used a modified version of the BPI, caution is further warranted in comparing ratings from this study with others using the BPI.…”
Section: Original Research and Contributionsmentioning
confidence: 74%
“…Nevertheless, some of the findings from these studies show comparable pain and functional impairment ratings as well as areas where the findings diverge. The cross-sectional study by Peleg et al 20 of 163 Israeli patients visiting a complementary medicine clinic because of pain showed similar ratings of current pain and interference with life domains compared with those of KPCO patients. Vallerand et al 21 surveyed 595 residents from urban, suburban, and rural communities and showed pain ratings generally comparable to those reported by KPCO patients.…”
Section: Original Research and Contributionsmentioning
confidence: 90%
“…One cross-sectional study showed that about 23% were hoping to avoid invasive procedures, 34% were disappointed by conventional medicine, and about 50% were using CAM together with conventional treatments (Peleg et al, 2011). A cross-sectional study in Singapore concluded the prevalence of CAM use in those with chronic pain is higher than in a general population.…”
Section: Introductionmentioning
confidence: 99%